Release of flagellar filament-hook-rod complex by a Salmonella typhimurium mutant defective in the M ring of the basal body. - Okino, H (1989)
A Salmonella typhimurium strain possessing a mutation in the fliF gene (coding for the component protein of the M ring of the flagellar basal body) swarmed poorly on a semisolid plate. However, cells grown in liquid medium swam normally and did not show any differences from wild-type cells in terms of swimming speed or tumbling frequency. When mutant cells were grown in a viscous medium, detached bundles of flagellar filaments as long as 100 microns were formed and the cells had impaired motility. Electron microscopy and immunoelectron microscopy revealed that the filaments released from the cells had the hook and a part of the rod of the flagellar basal body still attached. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis and two-dimensional gel electrophoresis showed that the rod portion of the released structures consisted of the 30-kilodalton FlgG protein. Double mutants containing this fliF mutation and various che mutations were constructed, and their behavior in viscous media was analyzed. When the flagellar rotation of the mutants was strongly biased to either a counterclockwise or a clockwise direction, detached bundles were not formed. The formation of large bundles was most extreme in mutants weakly biased to clockwise rotation.